2011 IEEE Third International Conference on Cloud Computing Technology and Science 2011
DOI: 10.1109/cloudcom.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Amazon EC2 Spot Instance Pricing

Abstract: Cloud providers possessing large quantities of spare capacity must either incentivize clients to purchase it or suffer losses. Amazon is the first cloud provider to address this challenge, by allowing clients to bid on spare capacity and by granting resources to bidders while their bids exceed a periodically changing spot price. Amazon publicizes the spot price but does not disclose how it is determined.By analyzing the spot price histories of Amazon's EC2 cloud, we reverse engineer how prices are set and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 9 publications
2
163
0
1
Order By: Relevance
“…However, since Amazon reveals no detailed pricing information, it remains unclear how the spot price is determined. Despite Amazon's claim that the price is calculated based on market demand and supply [1], some recent works conjecture that the price is in fact artificially set via some random process [9], [12]. In this paper, we consider periodic uniform-price auctions, as they share similar pricing forms as the EC2 spot market.…”
Section: Related Workmentioning
confidence: 99%
“…However, since Amazon reveals no detailed pricing information, it remains unclear how the spot price is determined. Despite Amazon's claim that the price is calculated based on market demand and supply [1], some recent works conjecture that the price is in fact artificially set via some random process [9], [12]. In this paper, we consider periodic uniform-price auctions, as they share similar pricing forms as the EC2 spot market.…”
Section: Related Workmentioning
confidence: 99%
“…However, other authors found that the spot price variation in Amazon EC2 over time does not seem to follow any particular law [24]. It has also been observed in [25] that Amazon may be artificially intervening in the prices by setting a reserve price and generating prices at random, thus complicating even more the prediction of spot price variations.…”
Section: Introductionmentioning
confidence: 95%
“…Such an interesting result is only at a first glance surprising and stems from a sort of emergent behavior of the community, homogeneous and willing to minimize its regret. This situation motivates quite easily why a market-driven strategy could turn to be unprofitable for an IaaS provider and why, indeed, Amazon EC2 does not apply it [11].…”
Section: A Community and Market-driven Approachmentioning
confidence: 99%
“…An interesting reverse engineering analysis of the price of Amazon EC2 spot instances was conducted by Ben-Yehuda et al [11]. By analyzing the spot price history, they built a model generating prices consistent with existing price traces.…”
Section: Related Workmentioning
confidence: 99%